Mulabandha yoga therapy and its utility in cases of urinary incontinence in females: A randomized clinical trial - Km Sweta; Amrit Godbole; H H Awasthi; Uma Pandey (Wolters Kluwer Medknow Publications, 2020)
Background: Urinary incontinence (UI) is a common condition in women, with prevalence ranging from 8.5% to 38% depending on age, parity, and definition. This problem is more common in Asian countries, where women usually do not seek treatment for their reproductive health problems and do not vocalize their symptoms. Mulabandha yoga therapy (MYT) is said to be effective for the management of UI. Hence, it was tried to see the effects of this method in females. Aims and Objective: The aim and objective was to study the effect of yoga therapy in female patients for 3 months suffering from UI. Methods: An intervention of Mulabandha yoga therapy (Contraction of pelvic group muscles) for the period of three months has been done by interventional group. Design: Participants were allocated into two groups by generating random allocation sequence. Participants: Fifty female participants were divided into two groups, i.e., interventional and noninterventional (control) groups. The interventional group (n = 25) received an intensive supervised MYT protocol along with medication and the control group (n = 25) received only oral medicines. Outcome Measures: Improvement in UI symptoms was assessed using the Questionnaire for Urinary Incontinence Diagnosis (QUID). Both groups were evaluated at the beginning of the study and after 12 weeks. Results: At the completion of study, data received from all the fifty women were included in the analysis. Percentage improvement in the QUID mean change was 58.72 in the intervention group and 21.54 in the control group. Intergroup comparison (Mann-Whitney test) was found to be statistically significant in the intervention group (p < 0.00), whereas it was nonsignificant in the control group (p = 0.14). Conclusion: MYT plays a significant role in the improvement of UI symptoms.